The elusive elixir - Pandian, Gigi, 1975- (Pandian, Gigi, 1975- Accidental alchemist., 2017)
"Dorian Robert-Houdin, the three-and-a-half-foot gargoyle chef who fancies himself a modern-day Poirot, is slowly turning into stone, and it's up to Zoe Faust to unravel the alchemical secrets that can save him. When they discover that a long-lost stone gargoyle with a connection to Dorian has reappeared in Europe, the stakes are even higher. From Portland to Paris, Zoe searches for the hidden knowledge she needs, but a cold case that harkens back to 1942 throws her off course. With an ailing friend desperately trying to discover his own Elixir of Life and a new romantic interest offering the first chance at love she's had in nearly a century, Zoe is torn between a dangerous form of alchemy and her desire for a normal life."--Amazon.com